Chemical composition of the essential oil of Morina longifolia wall. Leaves (2013)
Essential oil from the leaves of Morina longifolia was isolated (yield 1.43%) using the hydro-distillation method and analysed for its chemical composition by capillary GC-FID and GC-MS. The oil showed the presence of 47 compounds representing 82.29 % area of total chromatogram. The oil was dominated by sesquiterpenes amounting to 53.02% with germacrene D (20.74%), α-cadinol (4.09%)l, and germacrene D-4-ol (3.73%) as major constituents. The composition and characteristics odor of the oil is indicative of its use in fragrance applications.